Optical coherence tomography in the diagnosis and treatment of spontaneous coronary artery dissection. - Lim, C; Banning, A; Channon, K (2010)
The diagnosis of spontaneous coronary artery dissection (SCAD) is not always readily apparent on coronary angiography. Even if the diagnosis is suspected, angiography often conveys limited information about the underlying pathology, much of which is crucial for successful percutaneous coronary intervention (PCI). Due to the dissection flap and the resultant double lumen, SCAD poses unique challenges for PCI, specifically in securing wire access to the true lumen without propagation of the dissection. Optical coherence tomography (OCT) is a wire-based intravascular imaging modality with a high resolution of 10-20 µm. We present a case demonstrating the use of OCT in emergency PCI of SCAD, where OCT was integral not only to the diagnosis of SCAD, but also to successful PCI of the condition. It is a valuable aid to PCI in cases where there is uncertainty regarding the precise guidewire location, proving its use in the cardiac catheterization laboratory beyond that of merely a diagnostic tool.